polyhomeotic regulatory sequences induce developmental regulator-dependent variegation and targeted P-element insertions in Drosophila. - Fauvarque, M.O.; Dura, J.M. (Genes & Development, 1993)
Variegation of the miniwhite gene is observed in a euchromatic context in transformant lines that contain a P transposon including regulatory sequences of the polyhomeotic (ph) gene upstream of the resident miniwhite gene (P[ph]). This variegated phenotype is not affected by most of the genetic modifiers of heterochromatic position-effect variegation (PEV) nor by removal of the Y chromosome. Interestingly, it is sensitive to ph and Polycomb (Pc) mutations, which are known to affect homeotic gene regulation. Regulatory DNA of ph can also mediate transvection of the miniwhite gene. This transvection is abolished in a ph but not in a zeste mutant background. In addition, P[ph] inserts preferentially in sites corresponding to PH/PC protein-binding sites as defined at the polytene chromosome level. These insertions induce an unusually high proportion of mutations in genes affecting homeotic gene regulation. In particular, one insertion is located within the tramtrack locus, which is thought to regulate fushi tarazu, an Ultrabithorax activator. We suggest that a multimeric complex containing PH and PC proteins, at a minimum, causes a local and clonally inherited heterochromatinization, which maintains the repressed state of transcription of the homeotic genes.